Komparasi Makna Baṣara dalam Al-Qur’an dengan Extra Sensory Perception - Pamukti, Aryani; Soleh, Achmad Khudori (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, 2023)
People who experience phenomena that cannot be explained logically are usually said to have a sixth sense and are able to see through their inner eyes or scientifically known as extrasensory perception. In some cultures, and beliefs, someone who has abilities beyond the senses usually gets a high position in society and is trusted to provide consideration in deciding a problem. The ability to see through the eyes of the heart is mentioned in the Qur’an through the Baṣara verse. The purpose of this research is to find out the meaning of Baṣara in the Qur’an and extrasensory perception. The method used in this research is a qualitative approach which is library research and the data analysis used is descriptive analysis. The results of this study indicate that Baṣara verses and their istiqaq in the Qur’an contain 148 verses. Baṣara is an obligatory attribute of Allah that we must believe in, but it is also a human trait. Extra sensory perception is a person’s ability to perceive a stimulus that is present not from the main senses originating from the soul and is responded to through the soul, while the extra forms of sensory perception are telepathy, clairvoyance, precognition, and retrocognition. Baṣara’s view is obtained based on a person’s high faith, while extra sensory perception can be owned by everyone, but you need to be vigilant. Someone who gets karomah from Allah is called having the ability baṣirah.